Sphingomonas chlorellae sp. nov., Isolated from Outdoor Photobioreactor Culturing Chlorella sp. HS2 with Soy Sauce Wastewater - Won-Suk Choi; So-Ra Ko; Yun-Kyoung Kwon; Hayoung Lee; Seonah Jeong; Hee-Sik Kim; Chi-Yong Ahn (Current Microbiology, 2026)

Growth inhibition of harmful cyanobacterium Microcystis by picocyanobacterium Cyanobium: transcriptome-based interaction analysis - Min-Seong Kim; So-Ra Ko; Mingyeong Kang; Seonah Jeong; Hayoung Lee; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Harmful Algae, 2025)

Ferrovibrio plantarum sp. nov., Isolated from the Co-culture of Myriophyllum spicatum (Water Milfoil) and Microcystis aeruginosa - Mingyeong Kang; Seonah Jeong; Ve Van Le; So-Ra Ko; Min-Seong Kim; Dong-Yun Choi; Chi-Yong Ahn (Current Microbiology, 2025)

Selective cyanobactericidal activity of Nocardioides convexus MS16 against Microcystis aeruginosa, mediated by direct attack - Seonah Jeong; Ve Van Le; So-Ra Ko; Mingyeong Kang; Min-Seong Kim; Zhun Li; Chi-Yong Ahn (Algal Research, 2025)

Genomic and transcriptomic insights into benzoate and 4-hydroxybenzoate degradation in Arthrobacter sp. PAMC25564 isolated from cryoconite - Nisha Ghimire; Byeollee Kim; So-Ra Han; Jun Hyuck Lee; Tae-Jin Oh (International Biodeterioration & Biodegradation, 2025)

Roseateles microcysteis sp. nov., Isolated from Co-cultivation of Microcystis aeruginosa and Myriophyllum spicatum - Min-Seong Kim; Seonah Jeong; Mingyeong Kang; So-Ra Ko; Ve Van Le; Dong-Yun Choi; Chi-Yong Ahn (Current Microbiology, 2025)

Undibacterium cyanobacteriorum sp. nov., an auxin-producing bacterium isolated from fresh water during cyanobacterial bloom period - Ve Van Le; So-Ra Ko; Loan Thi Thanh Nguyen; Jin-Cheol Kim; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Antonie van Leeuwenhoek, 2024)

Microcystis abundance is predictable through ambient bacterial communities: A data-oriented approach - Mingyeong Kang; Dong-Kyun Kim; Ve Van Le; So-Ra Ko; Jay Jung Lee; In-Chan Choi; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Journal of Environmental Management, 2024)

Succession of particle-attached and free-living bacterial communities in response to microalgal dynamics induced by the biological cyanocide paucibactin A - Ve Van Le; So-Ra Ko; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Chemosphere, 2024)

Effect of rainfall in shaping microbial community during Microcystis bloom in Nakdong River, Korea - Mingyeong Kang; Ve Van Le; So-Ra Ko; Seong-Jun Chun; Dong-Yun Choi; Yuna Shin; Kyunghyun Kim; Seung Ho Baek; Chi-Yong Ahn (Science of The Total Environment, 2024)

mTOR Plays an Important Role in the Stemness of Human Fetal Cartilage Progenitor Cells (hFCPCs) - Him-Cha Shin; Jiyoung Kim; So Ra Park; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2024)

Cultivation of Chlorella sp. HS2 using wastewater from soy sauce factory - Minsik Kim; Sang-Ah Lee; Jin-Ho Yun; So-Ra Ko; Dae-Hyun Cho; Hee Su Kim; Hee-Mock Oh; Hee-Sik Kim; Chi-Yong Ahn (Chemosphere, 2023)

A new cyclin-dependent kinase-9 inhibitor A09-003 induces apoptosis in acute myeloid leukemia cells with reduction of myeloid cell leukemia sequence-1 protein - Kyoung Mi Sim; So Young Kim; Supyong Hwang; Sojung Park; Bo Ra Lee; Kyyoub Nam; SeakHee Oh; Inki Kim (Chemico-Biological Interactions, 2023)

Characterization of weak layers in the Southwestern slope of Ulleung Basin with seismic data merging and inversion - Bo-Yeon Yi; Nyeon-Keon Kang; Seok-Hwi Hong; So-Ra Kim; Jiyoung Choi; Dong-Geun Yoo (Marine Geophysical Research, 2023)

Non-invasive mineral analysis of pigments of wall paintings in the Sungseonjeon Hall - Na Ra Lee; So Jin Kim; Dong Hyeok Moon (Geosciences Journal, 2023)

Human Fetal Cartilage-Derived Progenitor Cells Exhibit Anti-Inflammatory Effect on IL-1β-Mediated Osteoarthritis Phenotypes In Vitro - Jiyoung Kim; An Nguyen-Thuy Tran; Ji Young Lee; Sang-Hyug Park; So Ra Park; Byoung-Hyun Min; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2022)

Comparative analysis of genome-based CAZyme cassette in Antarctic Microbacterium sp. PAMC28756 with 31 other Microbacterium species - Sushma Gupta; So-Ra Han; Byeollee Kim; Chang-Muk Lee; Tae-Jin Oh (Genes & Genomics, 2022)

Complete genome sequencing and comparative CAZyme analysis of Rhodococcus sp. PAMC28705 and PAMC28707 provide insight into their biotechnological and phytopathogenic potential - Nisha Ghimire; So-Ra Han; Byeollee Kim; Sang-Hee Jung; Hyun Park; Jun Hyuck Lee; Tae-Jin Oh (Archives of Microbiology, 2021)

Sensitivity of Snowfall Characteristics to Meteorological Conditions in the Yeongdong Region of Korea - Yoo-Jun Kim; So-Ra In; Hae-Min Kim; Jin-Hwa Lee; Kyu Rang Kim; Seungbum Kim; Byung-Gon Kim (Advances in Atmospheric Sciences, 2021)

Comparative Analysis of the Expression of Chondroitin Sulfate Subtypes and Their Inhibitory Effect on Axonal Growth in the Embryonic, Adult, and Injured Rat Brains - Moon Hang Kim; So Ra Park; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2021)

Comparative Genomic Study of Polar Lichen-Associated Hymenobacter sp. PAMC 26554 and Hymenobacter sp. PAMC 26628 Reveals the Presence of Polysaccharide-Degrading Ability Based on Habitat - Nisha Ghimire; So-Ra Han; Byeollee Kim; Hyun Park; Jun Hyuck Lee; Tae-Jin Oh (Current Microbiology, 2020)

Complete genome sequence of Sphingobium sp. strain PAMC 28499 reveals a potential for degrading pectin with comparative genomics approach - So-Ra Han; Sung-Min Jang; Young Min Chi; Byeollee Kim; Sang-Hee Jung; Yung Mi Lee; Jun Uetake; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (Genes & Genomics, 2020)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

GM-CSF Enhances Mobilization of Bone Marrow Mesenchymal Stem Cells via a CXCR4-Medicated Mechanism - Jiyoung Kim; Na Kyeong Kim; So Ra Park; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2019)

Migration of lead and arsenic from food contact paper into a food simulant and assessment of their consumer exposure safety - Se-Jong Park; Jae Chun Choi; So-Ra Park; Heeju Choi; MeeKyung Kim; Jeongkwon Kim (Food Additives & Contaminants: Part A, 2018)

Characterization of Human Fetal Cartilage Progenitor Cells During Long-Term Expansion in a Xeno-Free Medium - Hwal Ran Kim; Jiyoung Kim; So Ra Park; Byoung-Hyun Min; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2018)

A multi-factor approach for process-based seabed characterization: example from the northeastern continental margin of the Korean peninsula (East Sea) - Deniz Cukur; In-Kwon Um; Jong-Hwa Chun; So-Ra Kim; Gwang-Soo Lee; Yuri Kim; Gee-Soo Kong; Senay Horozal; Seong-Pil Kim (Geo-Marine Letters, 2018)

Analysis of water balance by surface–groundwater interaction using the SWAT model for the Han River basin, South Korea - So Ra Ahn; Seong Joon Kim (Paddy and Water Environment, 2018)

Erratum to: Characteristics and Cardiomyogenic Potential of Rat Fetal Cardiac Progenitor Cells at Different Developmental Stage - Tung Nguyen Thanh; Him Cha Shin; Hwal Ran Kim; So Ra Park; Jiyoung Kim; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2017)

Characteristics and Cardiomyogenic Potential of Rat Fetal Cardiac Progenitor Cells at Different Developmental Stage - Tung Nguyen Thanh; Him Cha Shin; Hwal Ran Kim; So Ra Park; Jiyoung Kim; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2017)

Hydrologic Evaluation of River Basin Scale Tillage Effects on Non‐Point Source Loads from Upland Crop Areas † - So Ra Ahn; Joong Dae Choi; Seong Joon Kim (Irrigation and Drainage, 2016)
This study used the Hydrological Simulation Program—Fortran (HSPF) model to evaluate the river basin scale effects of nonpoint source (NPS) pollution loads caused by tillage and no‐tillage applications to upland crop areas. The study site was the Byulmi‐cheon river basin (1.21 km 2 ) of South Korea. Hourly rainfall, discharge and stream water quality data for 2 years (2012–2013) were collected at the river basin outlet. The HSPF model under tillage conditions was calibrated using 23 rainfall events with an average Nash–Sutcliffe model efficiency value for runoff of 0.61 and determination coefficients for sediment, total nitrogen (T‐N) and total phosphorus (T–P) of 0.58, 0.61 and 0.62 respectively. The field experiment results from the no‐tillage plots with slopes of 3 and 8% under radish and sesame cultivation showed decreases in the runoff ratio, sediment, T‐N and T–P of 10.8, 81.7, 11.9 and 17.1% respectively. The HSPF model parameters soil bulk density (BD) and soil infiltration capacity (INFILT) were controlled for the upland crop areas during the evaluation of the no‐tillage effects. By increasing the parameter values from 1.33 Mg m −3 BD and 4.1 mm h −1 INFILT for the tillage condition to 1.90 Mg m −3 BD and 8.9 mm h −1 INFILT for the no‐tillage condition, the river basin runoff ratio and sediment, T‐N and T–P values were reduced by 10.3, 56.7, 18.3 and 35.9% respectively. Copyright © 2016 John Wiley & Sons, Ltd.

Assessment of hydrological changes in a river basin as affected by climate change and water management practices, by using the cat model - Cheol Hee Jang; Hyeon Jun Kim; So Ra Ahn; Seong Joon Kim (Irrigation and Drainage, 2016)
This study describes the applicability of the Catchment hydrologic cycle Assessment Tool (CAT) for improving the water cycle in a river basin, and suggests appropriate water cycle improvement methods for adapting the impact of future climate change on river basin hydrology. For future assessment, the Gyeongan‐Cheon River Basin located in the north‐eastern part of South Korea was selected. To evaluate future water cycle improvement, the data from two general circulation models (GCMs), MIROC3.2 hires and HadCM3 with A1B and B1 scenarios, were adopted and downscaled by using the Long Ashton Research Station–Weather Generator (LARS‐WG) after bias correction with 30 year (baseline; 1970 ~ 2000) ground measurements. The future annual surface runoff, groundwater flow and evapotranspiration changed up to +49, −45 and +44% in the late twenty‐first‐century of MIROC3.2hires A1B scenario and up to +56, −44 and +47% in the late twenty‐first‐century of HadCM3 A1B scenario. Under the condition of water cycle improvement are included by facilities, the hydrological cycle was enhanced by increasing groundwater flow and evapotranspiration, and decreasing surface runoff. The future annual surface runoff, groundwater flow and evapotranspiration were improved by −38, +13 and +24% in the late twenty‐first century MIROC3.2hires A1B scenario, and by −38, +13 and +25% for the HadCM3 A1B scenario. Copyright © 2016 John Wiley & Sons, Ltd.

Assessing drought threats to agricultural water supplies under climate change by combining the SWAT and MODSIM models for the Geum River basin, South Korea - So Ra Ahn; Jae Hak Jeong; Seong Joon Kim (Hydrological Sciences Journal, 2016)

Assessment of Climate Change Impacts on the Future Hydrologic Cycle of the Han River Basin in South Korea Using a Grid‐Based Distributed Model - So Ra Ahn; Seong Joon Kim (Irrigation and Drainage, 2016)
The purpose of this study is to assess the impacts of climate change on the hydrologic cycle of the Han River Basin in South Korea using the Projection of Hydrology via the Grid‐based Assessment for Climate Change (PGA‐CC) model. PGA‐CC is a physically based continuous, long‐term, distributed model. The model was calibrated and validated using 9 years (2001–2009) of inflow data from two sub‐basins to reservoirs (the Chungju Reservoir and Soyang Reservoir) in the Han River Basin with a 4 km spatial resolution. The average Nash–Sutcliffe model efficiencies of the Chungju and Soyang reservoirs were 0.57 and 0.71, and the average coefficients of determination were 0.65 and 0.72, respectively. The applicability of the PGA‐CC model was tested by assessing the future river basin hydrology with the HadGEM3‐RA AR5 4.5 and 8.5 climate change scenarios. The annual total discharge from the RCP 4.5 scenario in the 2080s showed a change of up to +33.0% based on the 1070 mm yr −1 value from the baseline period (1980–2009) due to a +28.1% increase in precipitation. The annual evapotranspiration from the RCP 8.5 scenario showed an increase of up to 46.2% compared to the baseline period of 357 mm yr −1 due to a temperature increase of 5.4 °C. Copyright © 2016 John Wiley & Sons, Ltd.

Two new phenolic compounds from the leaves of Alnus sibirica Fisch. ex Turcz. - Manh Heun Kim; Kwan Hee Park; So Ra Kim; Kwang Jun Park; Myeong Hwan Oh; Jun Hyeok Heo; Ki Hoon Yoon; Jun Yin; Kyu Hyung Yoon; Min Won Lee (Natural Product Research, 2016)

A Method for Cell Culture and Maintenance of Ammonia-Oxidizing Archaea in Agar Stab - Yeon-Jin Chu; Jin-Young Lee; So-Ra Shin; Geun-Joong Kim (Indian Journal of Microbiology, 2015)

Fabrication of an osteochondral graft with using a solid freeform fabrication system - Soon Sim Yang; Woo Hee Choi; Bo Ram Song; He Jin; Su Jeong Lee; Su Hee Lee; Junhee Lee; Young Jick Kim; So Ra Park; Sang-Hyug Park; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2015)

Therapeutic possibility of human fetal cartilage-derived progenitor cells in rat arthritis model - Su Jeong Lee; Hyun Ju Oh; Minh-Dung Truong; Kyi Beom Lee; Jiyoung Kim; Young Jick Kim; So Ra Park; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2015)

Trichosanthes kirilowii ameliorates cisplatin-induced nephrotoxicity in both in vitro and in vivo - Chang-Seob Seo; Tae-Won Kim; Young-Jung Kim; So-Ra Park; Hyekyung Ha; Hyeun-Kyoo Shin; Ju-Young Jung (Natural Product Research, 2015)

Evaluation of MODIS NDVI and LST for indicating soil moisture of forest areas based on SWAT modeling - Jong-Yoon Park; So-Ra Ahn; Soon-Jin Hwang; Cheol-Hee Jang; Geun-Ae Park; Seong-Joon Kim (Paddy and Water Environment, 2014)

Granulocyte Macrophage Colony-Stimulating Factor Shows Anti-apoptotic Activity via the PI3K–NF-κB–HIF-1α–Survivin Pathway in Mouse Neural Progenitor Cells - Jung Kyoung Choi; Kil Hwan Kim; So Ra Park; Byung Hyune Choi (Molecular Neurobiology, 2014)

Mesenchymal stem cells for treatment of neurological disorders: a paracrine effect - Moonhang Kim; Kil Hwan Kim; So Ra Park; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2013)

Comparison between subchondral bone change and cartilage degeneration in collagenase- and DMM- induced osteoarthritis (OA) models in mice - Byoung Ju Kim; Byung Hyune Choi; Long Hao Jin; So Ra Park; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2013)

Esculetin promotes type I procollagen expression in human dermal fibroblasts through MAPK and PI3K/Akt pathways - Jung Hae Park; So Ra Kim; Hyun Ju An; Woo Jin Kim; Myeon Choe; Jeong A. Han (Molecular and Cellular Biochemistry, 2012)

Determination of PDE-5 inhibitors and appetite suppressants in adulterated dietary supplements using LC/PDA and LC/MS - So-ra Park; Jin Gyun Lee; Si Hun Roh; Gyudong Kim; Chan Hyeok Kwon; Hee Ra Park; Ki Sung Kwon; Deukjoon Kim; Sung Won Kwon (Food Additives & Contaminants Part B-Surveillance, 2012)

Granulocyte macrophage-colony stimulating factor shows anti-apoptotic activity in neural progenitor cells via JAK/STAT5-Bcl-2 pathway - Jung Kyoung Choi; Kil Hwan Kim; Hyeonseon Park; So Ra Park; Byung Hyune Choi (Apoptosis, 2011)

Erratum to: Estimation of carbon storage based on individual tree detection in Pinus densiflora stands using a fusion of aerial photography and LiDAR data - So-Ra Kim; Doo-Ahn Kwak; Woo-Kyun Lee; Yowhan Son; Sang-Won Bae; Choonsig Kim; Seongjin Yoo (Science China Life Sciences, 2010)

Estimation of carbon storage based on individual tree detection in Pinus densiflora stands using a fusion of aerial photography and LiDAR data - So-Ra Kim; Doo-Ahn Kwak; Woo-Kyun oLee; Yowhan Son; Sang-Won Bae; Choonsig Kim; Seongjin Yoo (Science China Life Sciences, 2010)

Estimating stem volume and biomass of Pinus koraiensis using LiDAR data - Doo-Ahn Kwak; Woo-Kyun Lee; Hyun-Kook Cho; Seung-Ho Lee; Yowhan Son; Menas Kafatos; So-Ra Kim (Journal of Plant Research, 2010)

CHARACTERIZATION OF SUBPOPULATED ARTICULAR CHONDROCYTES SEPARATED BY PERCOLL DENSITY GRADIENT - BYOUNG-HYUN MIN; HYEON JOO KIM; HANJO LIM; SO RA PARK (In Vitro Cellular & Developmental Biology - Animal, 2002)